A comparison of the community diversity of foliar fungal endophytes between seedling and adult loblolly pines (Pinus taeda). Issue 10 (October 2015) - Oono, Ryoko; Lefèvre, Emilie; Simha, Anita; Lutzoni, François
Abstract: Fungal endophytes represent one of the most ubiquitous plant symbionts on Earth and are phylogenetically diverse. The structure and diversity of endophyte communities have been shown to depend on host taxa and climate, but there have been relatively few studies exploring endophyte communities throughout host maturity. We compared foliar fungal endophyte communities between seedlings and adult trees of loblolly pines ( Pinus taeda ) at the same seasons and locations by culturing and culture-independent methods. We sequenced the internal transcribed spacer region and adjacent partial large subunit nuclear ribosomal RNA gene (ITS–LSU amplicon) to delimit operational taxonomic units and phylogenetically characterize the communities. Despite the lower infection frequency in seedlings compared to adult trees, seedling needles were receptive to a more diverse community of fungal endophytes. Culture-free method confirmed the presence of commonly cultured OTUs from adult needles but revealed several new OTUs from seedling needles that were not found with culturing methods. The two most commonly cultured OTUs in adults were rarely cultured from seedlings, suggesting that host age is correlated with a selective enrichment for specific endophytes. This shift in endophyte species dominance may be indicative of a functional change between these fungi and their loblolly pine hosts. Highlights: We studied the fungal endophyte diversity in seedlings and trees of loblolly pines. Isolation frequency is lower in seedlings compared to adult trees. Fungal diversity is greater in seedlings compared to adult trees. Some OTUs common in adult tree needles were rare in seedlings. Shift in structure may indicate a functional change in the fungal community.